Establishing the integrated science of movement: bringing together concepts and methods from animal and human movement analysis. Issue 7 (3rd July 2021) - Demšar, Urška; Long, Jed A.; Benitez-Paez, Fernando; Brum Bastos, Vanessa; Marion, Solène; Martin, Gina; Sekulić, Sebastijan; Smolak, Kamil; Zein, Beate; Siła-Nowicka, Katarzyna
ABSTRACT: Movement analysis has become an integral part of many disciplines, yet with relatively little overlap. A foresight paper in this journal entitled "Towards an integrated science of movement: converging research on animal movement ecology and human mobility science" argued for a better integration of concepts across the divide of animal and human movement, which would lead to the Integrated Science of Movement, but did so from a top-down perspective based on a series of expert workshops. We argue that for a solid establishment of the Integrated Science of Movement, a bottom-up approach is necessary, one based on existing literature which identifies similarities and differences across disciplines. We therefore review, compare, and contrast movement analysis methodologies from GIScience, movement ecology, geography, transportation, public health, computer science, and physics. We structure our review along the dichotomy of individual versus population-based movement or, using terminology from wildlife ecology, between the Lagrangian and Eulerian perspectives. We further introduce a new unifying framework for movement research that is sufficiently general to cover any type of movement study in any discipline and that spans the Lagrangian/Eulerian divide, with the ambitious goal to bridge the gap between disciplines and lay a solid foundation for a new Integrated Science of Movement.